The Relationship Between Knowledge, Attitudes, And Behavior And Infection Prevention During The Postnatal Period At The Kelapa Community Health Center, Kelapa District, West Bangka Regency In 2025 - Ivana Laira; Hidayani Hidayani; Meinasari Kurnia Dewi (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Postpartum infections are a major cause of maternal morbidity and mortality. Infection prevention is highly dependent on maternal behavior during the postpartum period, which is influenced by the level of knowledge and attitudes. At the Kelapa Community Health Center, challenges remain in optimizing self-managed infection prevention by postpartum mothers. This study aims to determine the relationship between knowledge, attitudes, and behaviors and postpartum infection prevention at the Kelapa Community Health Center, West Bangka Regency, in 2025. This study was quantitative with a cross-sectional design. The sample consisted of 56 postpartum mothers, selected using a total sampling technique. The research instrument used a questionnaire that had been tested for validity and reliability. Data were analyzed using univariate and bivariate methods using the Chi-Square test (α = 0.05). The bivariate analysis revealed a significant relationship between knowledge (p = 0.000), attitudes (p = 0.000), and behavior (p = 0.000) and postpartum infection prevention. A Cramer's V value of 0.522 indicates a strong relationship between behavioral variables and infection prevention measures. Mothers with positive behaviors were 16 times more likely to adhere to infection prevention measures than those with poor behaviors. There is a significant relationship between knowledge, attitudes, and behavior and the prevention of postpartum infections at the Kelapa Community Health Center. It is recommended that healthcare workers enhance education for postpartum mothers regarding infection prevention through continuous counseling, as well as encourage mothers to adopt clean and healthy living behaviors during the postpartum period. Keywords        :  INTRODUCTION Knowledge, Attitudes, Behavior, Postpartum Infection Prevention.